First evaluation of the Behavioral Addiction Indoor Tanning Screener (BAITS) in a nationwide representative sample - Diehl, Katharina; Görig, Tatiana; Schneider, Sven (British journal of dermatology, 2018)
Background Evidence suggests that indoor tanning may have addictive properties. However, many instruments for measuring indoor tanning addiction show poor validity and reliability. Recently, a new instrument, the Behavioral Addiction Indoor Tanning Screener (BAITS), has been developed. Objectives To test the validity and reliability of the BAITS by using a multimethod approach. Methods We used data from the first wave of the National Cancer Aid Monitoring on Sunbed Use, which included a cognitive pretest (August 2015) and a Germany-wide representative survey (October to December 2015). In the cognitive pretest 10 users of tanning beds were interviewed and 3000 individuals aged 14-45 years were included in the representative survey. Potential symptoms of indoor tanning addiction were measured using the BAITS, a brief screening survey with seven items (answer categories: yes vs. no). Criterion validity was assessed by comparing the results of BAITS with usage parameters. Additionally, we tested internal consistency and construct validity. Results A total of 19·7% of current and 1·8% of former indoor tanning users were screened positive for symptoms of a potential indoor tanning addiction. We found significant associations between usage parameters and the BAITS (criterion validity). Internal consistency (reliability) was good (Kuder-Richardson-20, 0·854). The BAITS was shown to be a homogeneous construct (construct validity). Conclusions Compared with other short instruments measuring symptoms of a potential indoor tanning addiction, the BAITS seems to be a valid and reliable tool. With its short length and the binary items the BAITS is easy to use in large surveys.